Analysis and Potential Value of Compounds Extracted From Star Ruby, Rio Red, and Ruby Red Grapefruit, and Grapefruit Juice Processing Residues via Steam Explosion - Dorado, Christina; Cameron, Randall G.; Manthey, John A.; Bai, Jinhe; Ferguson, Kyle L. (Frontiers in Nutrition, 2021)
Culled whole grapefruit (WG) and grapefruit juice processing residues (GP) are currently incorporated into low cost animal feed. If individual chemical components found within these side streams could be recovered as high value co-products, this would improve the overall value of the grapefruit crop. In this work, pectic hydrocolloids, sugars, volatiles, phenolics, and flavonoids were extracted from Star Ruby, Rio Red, and Ruby Red GP and WG using a continuous pilot scale steam explosion system. Up to 97% of grapefruit juice oils and peel oils could be volatilized and contained 87.06-93.73% d-limonene. The recovery of pectin, as determined by galacturonic acid content, was between 2.06 and 2.72 g · 100 g-1 . Of the phenolics and flavonoids analyzed in this study, narirutin and naringin were extracted in the amounts of up to 10,000 and 67,000 µg g-1, respectively.